Microstructure and mechanical properties of nanocomposite (Ti,Si,Al)N coatings - Carvalho, S. (2001)
In this work (Ti,Si,Al)N films were deposited using only rf or a combination of rf and d.c. reactive magnetron sputtering. Chemical composition, thickness, film structure and mechanical properties of the films were investigated by means of Rutherford backscattering (RBS), electron microprobe analysis (EPMA), ball-cratering, X-ray diffraction (XRD) and ultramicroindentation, respectively. All samples showed high hardness values, exceeding, in some cases, 50 GPa. XRD results revealed the formation of a mixture of two phases whose structure is similar to TiN. One phase is noted as being TiN bulk with a lattice parameter of 0.428 nm and develops only in conditions of high surface mobility. This behaviour can be associated with the segregation of the SiNx phase, though the formation of an amorphous AlN phase cannot be excluded. Another phase, which is noted as Ti---Si---Al---N (a[approximate]0.420 nm), where Si and Al atoms substitute the Ti atoms on the TiN lattice, develops in situations of lower surface mobility. The thermal stability of these coatings was studied by thermal treatments in a vacuum atmosphere, where it was found that a small increase in hardness was obtained after 1 h heat treatment at 800°C.